Chile - Institutional Design for an Effective Education Quality Assurance - World Bank (Washington, DC, 2012)
The main objective of this report is to present the Government of Chile with policy options related to the institutional distribution of roles and responsibilities for effective quality assurance in education. Following the introduction, the report is structured as follows. Chapter II presents background information on the evolution of Chile's education system since 1980. This information, together with an analysis of the current situation of the education sector, describes the motivation for the study and demonstrates the urgent need to shift the focus in education policy to quality assurance. Chapter III describes the conceptual framework developed for the analysis of how successful systems carry out education quality assurance. The framework developed identifies education participants, including: students; teachers; principals and school administrators; schools; local governments (districts, municipalities); regional governments (states, provinces); and the national government. Chapter IV applies the framework to the nine education systems selected as comparisons and presents a summary of the quality assurance functions and institutions in each selected education system. Chapter V describes the four alternative instructional visions for quality assurance in education developed as a result of the international review. Finally, Chapter VI presents policy options for the distribution of roles and responsibilities for education quality assurance across individuals and/or institutions, which vary depending on the instructional vision followed.